2009
DOI: 10.1007/s00467-009-1124-y
|View full text |Cite
|
Sign up to set email alerts
|

The transition of kidney transplant recipients: a work in progress

Abstract: This study examined the process of transition for pediatric kidney transplant recipients who were transferred from the Royal Children's Hospital to adult health services between October 2005 and September 2006. A retrospective review of case notes was used to identify graft stability 12 months before and after transfer. A patient satisfaction questionnaire was sent to all transferred patients in October 2007. Eleven patients were identified with a mean age of 19.5 years. Nine of these 11 patients remained medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
2
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(104 citation statements)
references
References 18 publications
6
91
2
5
Order By: Relevance
“…A number of studies have focused on the views of chronically ill adolescents and their parents, but a disease-specific approach was mostly applied [4,5,15,16,24,26]. It was concluded that this disease-specific focus does not allow generalization of the results for transition recommendations [8].…”
Section: Ahc Adult Health Carementioning
confidence: 99%
“…A number of studies have focused on the views of chronically ill adolescents and their parents, but a disease-specific approach was mostly applied [4,5,15,16,24,26]. It was concluded that this disease-specific focus does not allow generalization of the results for transition recommendations [8].…”
Section: Ahc Adult Health Carementioning
confidence: 99%
“…Among the 25 studies, 8 studied transition care for adolescents with diabetes, 27-32,39,40 5 studied adolescents who had undergone organ transplant 22,23,26,33,34 (all but 1 of these focused on kidney transplant), and 2 studied adolescents with sickle cell disease. 36,41 The remainder studied a variety of conditions including congenital adrenal hyperplasia, 21 HIV, 24 epilepsy, 25 juvenile idiopathic arthritis, 38 spina bifida, 42 cystic fibrosis, 37 or inflammatory bowel disease 43 or included a patient population comprising .1 chronic disease.…”
Section: Patients and Conditions Represented In Evaluation Studiesmentioning
confidence: 99%
“…36,41 The remainder studied a variety of conditions including congenital adrenal hyperplasia, 21 HIV, 24 epilepsy, 25 juvenile idiopathic arthritis, 38 spina bifida, 42 cystic fibrosis, 37 or inflammatory bowel disease 43 or included a patient population comprising .1 chronic disease. 20,35,44 Twelve studies were conducted in Europe: 8 in the United Kingdom, 21,22,29,32,35,36,39,50 1 in Germany, 33 1 in Spain, 40 and 2 in 26 One study included data from the United Kingdom and Australia. 24 Few studies used a concurrent comparison group.…”
Section: Patients and Conditions Represented In Evaluation Studiesmentioning
confidence: 99%
See 2 more Smart Citations